The Effect of Contextual Approach Type-Modeling on the Poetry Writing Skills of Fifth-Grade Students at SD Inpres 4/82 Mattaropuli, Bengo Subdistrict, Bone Regency - Rasyid, Putry Haryana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The poetry writing skills of elementary school students remain low due to conventional teaching methods and the lack of contextual approach usage. This study aims to describe the implementation of poetry writing learning with the contextual approach type-modeling, compare poetry writing skills between students who received treatment and those who did not, and analyze the effect of the contextual approach type-modeling on the poetry writing skills of fifth-grade students at SD Inpres 4/82 Mattaropuli. This research employs a quantitative method with a quasi-experimental nonequivalent control group design. The population consists of all 44 fifth-grade students, with a total sampling technique, comprising 22 students in the experimental group and 22 students in the control group. The research instruments include a learning outcome test, observation sheets, and documentation, while the data analysis techniques use descriptive and inferential statistics with SPSS version 24. The results show that the experimental group achieved an average posttest score of 78.64, higher than the control group, which obtained an average of 70.91, with a significance value of 0.029 (p < 0.05). This study concludes that the contextual approach type-modeling significantly affects students' poetry writing skills and can be considered an innovative and effective teaching strategy in elementary schools.